Guilt and Shame of What Might Have Been in Optimistic Offender Drivers - del Valle, Carlos Hugo Criado (Frontiers in Psychology, 2021)
Habitual offender drivers are required to recover points lost on their driving license by attending re-education courses, an experience that may, upon reflection of the incident in question, induce feelings of guilt or shame for the infractions they committed. A simulated driving task studied optimistic drivers to analyse the extent to which the controllability of the situational context influenced their use of internal and external factors regarding counterfactual thoughts and emotions such as guilt and shame. The study involved 160 drivers, of whom 54 were categorized as repeat offender drivers while 106 drivers attended courses for advanced professional driving licences. Participants drove along a route in a driving simulator, which had been previously adjusted for difficulty to generate a perception of high or low control. Based on the outcome obtained by participants in this stage, each driver had to report which resources they required to improve their outcome. Different factor ANOVAs were used to analyse our findings. The results indicated that optimistic offenders, unlike other groups (i.e., optimistic non-offender and pessimistic non-offender), thought that their results could have been better if external factors had been present (i.e., upward counterfactuals), both under conditions of high and low control. In fact, they believed their results would have been worse, had it not been for their internal resources (i.e., downward counterfactuals), especially under conditions of low control. Concerning emotions of guilt and shame, offender optimists had the lowest values in both conditions compared to the other groups. We may contend that optimistic offender drivers do not question their internal skills in view of the possibility of better outcomes. Moreover, they justify that if it were not for such internal skills, their results could have been worse. When they generated such thoughts, the emotions of guilt and shame were minimal.